Spesies Serangga Hama Padi dan Jagung serta Intensitas Serangannya di Kabupaten Lahat : Insect Pest Species on Rice and Maize and attack intensity in Lahat District - Novian Dwisatria Novian; Fitri Ramadhani (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
Insect pest attack on rice (Oryza sativa L.) and maize (Zea mays L.) could be potential in decrease production. This study aims to determine the insect pest species of rice and maize and attack intensity in Lahat District. This study was conducted using survey methods. The systematic random sampling methodology was adopted for sample population identification. Surveys were conducted in 3 subdistricts (Jarai, Pajar Bulan and Sukamerindu). Found three rice insect pests species. The third species was rice stem borer (Scirpophaga incertulas), leaf folder (Cnaphalocrosis medinalis) and rice bug (Leptocorisa sp). Found one maize insect pest species was fall armyworm (Spodoptera frugiperda). S. incertulas has attacked in 7 locations with low-intensity, Leptocorisa sp has attacked in 2 locations with low-intensity, C. medinalis has attacked in 1 location with low-intensity and S. frugiperda has attacked in 4 locations with low-intensity. Rice stem borer and fall armyworm can attack crop from the vegetative to generative phase.